Generación efectiva de carga para el sector transportador terrestre carretero en Colombia (2013)
This paper identifies the elements that characterize the collection and generation of effective cargo for the road transpor t sector in Colombia. The consolidation of the cargo market is at an appreciable distance from the place claimed by the sector regarding the generated supply and demand obtained. The sectorial analysis first establishes the international conditions in which supply and demand in the transpor t sector develop effectively. Second, the analysis explores the correlation between the economic structures of Colombia with the cargo activity, and finally, it discusses the market possibilities for the road cargo. One of the major observed shor tcomings relates to the scarce information and knowledge regarding the generation and securing of cargo.